Accumulation and aggregate formation of mutant superoxide dismutase 1 in canine degenerative myelopathy. (10th September 2015) - Nakamae, S.; Kobatake, Y.; Suzuki, R.; Tsukui, T.; Kato, S.; Yamato, O.; Sakai, H.; Urushitani, M.; Maeda, S.; Kamishina, H.
Highlights: SYN3554 reacted specifically to canine SOD1 expressed in cultured human cells. Canine mutant SOD1 but not wild-type SOD1 formed intracellular aggregates in vitro . SOD1 aggregates were observed in spinal neurons of mutant SOD1 homozygous dogs. Accumulation of mutant SOD1 was also found in reactive astrocytes. Abstract: Canine degenerative myelopathy (DM) is an adult-onset progressive neurodegenerative disorder that has recently been linked to mutations in the superoxide dismutase 1 (SOD1) gene. We generated a polyclonal antibody against canine SOD1 to further characterize the mutant SOD1 protein and its involvement in DM pathogenesis. This antibody (SYN3554) was highly specific to canine SOD1 and had the ability to reveal distinct cytoplasmic aggregates in cultured cells expressing canine mutant SOD1 and also in the spinal neurons of symptomatic homozygotes. A similar staining pattern was observed in asymptomatic homozygotes. SOD1 aggregates were not detected in the spinal neurons of heterozygotes; the accumulation of SOD1 was also detected in the reactive astrocytes of homozygotes and heterozygotes to a similar extent. Our results support the hypothesis that the cytoplasmic accumulation and aggregate formation of the mutant SOD1 protein, especially in astrocytes, are closely associated with the pathogenesis of DM. Therefore, this disease is regarded as a spontaneous large-animal model of SOD1-mediated amyotrophic lateral sclerosis in humans.